Antinociceptive and anti-inflammatory effects of cryptotanshinone through PI3K/Akt signaling pathway in a rat model of neuropathic pain. (25th May 2019) - Zhang, Wenjia; Suo, Meng; Yu, Guanling; Zhang, Mengyuan
Abstract: Peripheral nerve injuries often induce neuropathic pain through inflammation. Cryptotanshinone isolated from Salvia miltiorrhiza Bunge has been found to exert anti-inflammatory and analgesic activities. Thus, this study aimed to determine whether cryptotanshinone inhibits chronic constriction injury (CCI)-induced neuropathic pain in rats and its mechanism of action. CCI was performed by applying four loose ligatures to rat sciatic nerve. Cryptotanshinone was orally administered using pre-surgery, acute or repeated post-surgery treatment. The pain behaviors were determined by recording paw withdrawal mechanical threshold (PWMT) and thermal withdrawal latency (TWL). ELISA kits were used to measure interleukin (IL)-6, IL-1β and tumor necrosis factor (TNF)-α levels. qRT-PCR were performed to detect IL-6, IL-1β, TNF-α, PI3K and Akt expression. The phosphorylation of PI3K/Akt signaling was assessed using western blotting. PWMT and TWL in CCI group were higher than those in the control and sham groups. The acute post-CCI cryptotanshinone treatment but not pre-surgery treatment reduced PWMT and TWL. The effect of cryptotanshinone is more prominent when it was repeatedly administered after CCI. The CCI-induced increase in IL-6, IL-1β, TNF-α, PI3K/Akt signaling and their phosphorylation was also suppressed by repeated post-CCI cryptotanshinone treatment. This study suggested that post-CCI cryptotanshinone treatment reduced the surgery-induced neuropathic pain by suppressing PI3K/Akt signaling therefore inhibited inflammation. Highlights: Cryptotanshinone suppresses cytokine production in CCI rats. Cryptotanshinone reduces pain behaviors in CCI rts. PI3K/Akt signaling is involved in the effects of cryptotanshinone.